Transformasi Digital Pengelolaan Masjid Berbasis Inovasi Sistem Informasi dan Regulasi Nasional: Studi Evaluatif terhadap Aplikasi Menara Masjid BAZNAS - Muhammad Romadhona Kusuma (Jurnal Bangkit Indonesia, 2025)
Effective and efficient mosque management is a key factor in ensuring operational continuity and enhancing the quality of services provided to congregants. In line with the advancement of the digital era, the adoption of information technology in mosque governance has become an urgent necessity to support transparency, accountability, and administrative efficiency. This study aims to evaluate the effectiveness, transparency, as well as the innovative and regulatory aspects of the Menara Masjid Application developed by BAZNAS RI. The research method employed is exploratory in nature, involving literature review, field observation, and primary data collection from mosque administrators using the application. The results indicate that the application represents a community-based information system innovation that facilitates the management of congregational data, reporting of zakat, infaq, and sadaqah (ZIS), and real-time dissemination of activity information. In addition to promoting internal efficiency and transparency, the application is supported by national regulations through BAZNAS Chairman Regulation No. 005 of 2024, which reinforces its broad legitimacy and adoption. These findings affirm that digitalization through innovative and regulation-based information systems plays a strategic role in establishing modern, participatory, and sustainable mosque governance.